Happiness and the good life - Martin, Mike W., 1946- (New York ; Oxford : Oxford University Press, 2012)
Philosopher Mike W. Martin here examines the meaning of happiness by connecting it to the philosophical notion of 'the good life'. He explores the ways in which happiness interacts with all other dimensions of good lives.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Happiness; Well-being.; Conduct of life